AUDITOR CHARACTERISTICS AND AUDIT OPINION: DOES AFFECT THE AUDIT REPORT LAG? KARAKTERISTIK AUDITOR DAN PENDAPAT AUDIT: APAKAH MEMPENGARUHI LAPORAN AUDIT LAG? - Ni Kadek Lita Dwiyanti; Ni Wayan Rustiarini; Ni Putu Shinta Dewi (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose was to investigate the effect of auditor reputation, audit opinion, auditor switching, audit tenure on audit report lag. This research was conducted at 327 manufacturing companies listed on the Indonesia Stock Exchange for 2017-2019. The analysis technique used is multiple linear regression analysis. The results indicate that auditor reputation, audit opinion, and audit tenure have a negative effect on audit report lag, while auditor switching has a positive effect on audit report lag.